DEVICE AND METHOD FOR GENERATING RANDOM NUMBERS - Aitken Robert Campbell; Shifren Lucian (2017)
According to an embodiment of the present disclosure, a device and a method are provided. The device includes one or more resistive random access memory (ReRAM) elements. The device further includes a random number generator configured to generate a random number in dependence on impedance values of the one or more ReRAM elements.